2018
DOI: 10.1002/joa3.12085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrophysiological and pharmacological noninducibility following pulmonary vein isolation in patients with paroxysmal and persistent atrial fibrillation

Abstract: BackgroundTwo methods for testing inducibility of atrial fibrillation (AF)—atrial pacing and isoproterenol infusion—have been proposed to determine the endpoint of catheter ablation. However, the utility of the combination for testing electrophysiological inducibility (EPI) and pharmacological inducibility (PHI) is unclear.MethodsAfter pulmonary vein isolation (PVI), inducibility of atrial tachyarrhythmia was assessed with the dual methods in 291 consecutive patients with AF (65% paroxysmal) undergoing initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Leong‐Sit et al 16 investigated 144 patients with paroxysmal or persistent AF and found no statistical difference in recurrence rate regarding inducibility. The same results were reported from Santangeli et al 17 and Otsuka et al 20 Moreover, in a recent larger study from Lee et al 21 with 500 patients, inducibility was proven to be inferior to non‐PV triggers elimination in long‐term follow‐ups. Kawai et al 23 concentrated on patients with persistent AF and showed no benefit from non‐inducibility.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Leong‐Sit et al 16 investigated 144 patients with paroxysmal or persistent AF and found no statistical difference in recurrence rate regarding inducibility. The same results were reported from Santangeli et al 17 and Otsuka et al 20 Moreover, in a recent larger study from Lee et al 21 with 500 patients, inducibility was proven to be inferior to non‐PV triggers elimination in long‐term follow‐ups. Kawai et al 23 concentrated on patients with persistent AF and showed no benefit from non‐inducibility.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, recent studies have shown opposite results and have questioned the role of inducibility as an endpoint criterium for the success of AF ablation 16,17,20–23 . Leong‐Sit et al 16 investigated 144 patients with paroxysmal or persistent AF and found no statistical difference in recurrence rate regarding inducibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations